2016
DOI: 10.1016/j.jid.2016.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic Analysis of Sézary Syndrome Defines Patterns of Aberrant DNA Methylation and Identifies Diagnostic Markers

Abstract: Sézary syndrome (Sz) is a malignancy of skin-homing CD4(+) memory T cells that is clinically characterized by erythroderma, lymphadenopathy, and blood involvement. Distinction of Sz from erythroderma secondary to inflammatory skin diseases (erythrodermic inflammatory dermatosis [EID]) is often challenging. Recent studies identified recurrent mutations in epigenetic enzymes involved in DNA modification in Sz. Here we defined the DNA methylomes of purified CD4(+) T cells from patients with Sz, EID, and healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 43 publications
0
40
0
1
Order By: Relevance
“…These include several tumor suppressor genes as CDKN2A and Fas. The result further indicates that measuring promoter methylation of a singular gene, CMTM2 (chemokine‐like factor gene), is sufficient to distinguish Sézary syndrome from benign conditions . Besides complex molecular methods, it has been shown by Boonk et al that strong expression of Tox and PD1 is also well evaluable in the diagnosis of Sézary syndrome …”
Section: Aberrant Molecular Findings In Ctclmentioning
confidence: 95%
“…These include several tumor suppressor genes as CDKN2A and Fas. The result further indicates that measuring promoter methylation of a singular gene, CMTM2 (chemokine‐like factor gene), is sufficient to distinguish Sézary syndrome from benign conditions . Besides complex molecular methods, it has been shown by Boonk et al that strong expression of Tox and PD1 is also well evaluable in the diagnosis of Sézary syndrome …”
Section: Aberrant Molecular Findings In Ctclmentioning
confidence: 95%
“…Although it is not known exactly how the malignant T cells gain the capacity to impose these changes on the inflammatory environment, a series of recent data suggests that endogenous changes in the malignant T cells, including somatic mutations, somatic copy number variations, and epigenetic deregulation, may play a critical role [1925, 60, 151, 152]. Exogenous factors such as bacterial colonization and infection may also drive activation of pro-oncogenic mechanisms and inhibit anti-tumor immunity.…”
Section: Malignant Inflammation—a Hostile Takeovermentioning
confidence: 99%
“…Microarray data from tumorous MF tissue indicated that miR-34a is a candidate oncogenic molecule and miR-29a acts as a tumor suppressor, highlighting their regulatory role in the progression of MF (14). DNA methylation analysis has shown that Sézary syndrome is characterized by widespread yet distinct DNA methylation alterations, and that promoter hypermethylation of a single gene, chemokine-like factor chemokine-like factor-like MARVEL transmembrane domain containing 2 (CMTM2), was sufficient to accurately distinguish it from other erythrodermic inflammatory diseases (15). Together this evidence suggests epigenetic regulation may play a significant role on the pathogenesis and progression of MF.…”
mentioning
confidence: 99%